1994
DOI: 10.1089/cmb.1994.1.191
|View full text |Cite
|
Sign up to set email alerts
|

TRANSFAC Retrieval Program: A Network Model Database of Eukaryotic Transcription Regulating Sequences and Proteins

Abstract: DNA sequences that are involved in the control of gene expression in eukaryotes have been collected in conjunction with the proteins binding to and acting through them (TRANSFAC data set). To make these data accessible, the TRANSFAC retrieval program (TRP) has been developed as a database management system which is based upon the network model. This database model possesses particular advantages for data management of a complex structure. The aim of TRP is to provide an easily handled statistical basis for a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 12 publications
0
71
0
Order By: Relevance
“…However, understanding the mechanism(s) responsible for these effects will require the identification of the protein(s) binding within this domain. The nucleotide change at -374 resulting from a T-to-A substitution disrupts the binding of a variety of CTF/NF1 transcription factors established from the TRANSFAC database (24). A number of these proteins have been demonstrated to be involved in negative and positive gene regulation (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, understanding the mechanism(s) responsible for these effects will require the identification of the protein(s) binding within this domain. The nucleotide change at -374 resulting from a T-to-A substitution disrupts the binding of a variety of CTF/NF1 transcription factors established from the TRANSFAC database (24). A number of these proteins have been demonstrated to be involved in negative and positive gene regulation (25).…”
Section: Discussionmentioning
confidence: 99%
“…A matrix core is identified in each PFM by TRANSFAC as the five most conserved contiguous columns (highest confidence) (Knuppel et al (1994)). Extended cores were constructed to include columns that are adjacent to the cores and whose information content is greater than the information content of the highest entropy column in the core.…”
Section: Pfm-family Constructionmentioning
confidence: 99%
“…These binding sites are often represented as matrices, which are known in the literature under a variety of names: position weight matrices, position frequency matrices, alignment matrices, profiles, etc (Knuppel et al (1994), ; Lenhard and Wasserman (2002)). We refer to a matrix consisting of nucleotide counts per position as a position frequency matrix (PFM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1b, and comparisons of the discovered motifs with those described previously are shown in Supplementary Table 2. The discovered motifs provide significantly more information than was previously available; for 21 of the regulators there was no prior specificity information in the literature, and detailed probability matrices had previously been determined for only 17 regulators for which we report motifs 14 . For Cin5, which showed the largest difference between the computationally derived motif (TTACRTAA) and the previously reported site (TTACTAA; Supplementary Table 2), we found that the motif we report is also the preferred target in vitro ( Supplementary Fig.…”
mentioning
confidence: 99%